Sustainability and Transformation: Assessing the Success of Socioeconomic Development Programs for the Orang Asli in Enhancing Livelihood and Communities - Ramli, Rosfaraliza Azura; Mohamad Shaharudin Samsurijan; Ayodeji Emmanuel Oke (Journal of Social Transformation and Regional Development, 2024)
For several decades, the Orang Asli community in Malaysia has been marginalized and deprived of socioeconomic opportunities. As a response, the government and non-governmental organizations have implemented various socioeconomic development programs with the aim of fostering sustainability and transformation within the Orang Asli community.However, the effectiveness of these programs in transforming the Orang Asli community still needs to be made clear. Therefore, this study aims to evaluate the success of socioeconomic development programs in enhancing the socioeconomic status of the Orang Asli while promoting sustainability. The methodology of this study involved conducting interviews with members of the Orang Asli community in the state of Perak who reside in the Regrouping Plan (RPS). The findings revealed that some programs positively affected the Orang Asli community, contributing to both sustainability and improved livelihoods. Nevertheless, limitations and obstacles emerged during the implementation of these programs. Some hindrances include wildlife disturbance and no crops. The study proposed several recommendations to address these challenges and improve the effectiveness of socioeconomic development programs for the Orang Asli community with a focus on sustainability. Ultimately, this research contributes to the existing literature on the impact of development programs on marginalized communities. The insights provided in this study can help policymakers and practitioners design and implement more effective socioeconomic development programs that can enhance the lives and communities of the Orang Asli.